The in vivo metabolism of 5-(4-nitrophenyl)-4(2-phenylethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione in rats - (:unkn) unknown (MEDECINE ET HYGIENE, 2003)
The purpose of this study was to investigate the in vivo metabolism of 5-(4-nitrophenyl)-4-(2-phenylethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione. First its potential metabolites were synthesized and then the structures of the original compound were elucidated by UV, H-1-NMR and elemantary analysis. 40 mg dose was given intraperitoneally to rats. Blood samples were collected at 0, 0,5, 1, 2. 4. 6 12, 24, 48 and 72 hours after administration of substrate and blood was centrifuged to obtain plasma. The plasma were passed through a Sep-Pak C-18 cartridge. The samples were separated using HPLC on a reverse phase system. This study revealed reduction, N-acetylation and N-dealkylation as pathway of 5-(4-nitrophenyl)-4-(2-phenylethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione metabolism.
Keywords: 1,2,4-triazole-3-thione; in vivo metabolism; rat; ANTIFUNGAL ACTIVITIES; DERIVATIVES; ANTIBACTERIAL; HETEROCYCLES